2019
DOI: 10.1002/ana.25589
|View full text |Cite
|
Sign up to set email alerts
|

Hand posture as localizing sign in adult focal epileptic seizures

Abstract: Objective: The aim of this study was to identify specific ictal hand postures (HPs) as localizing signs of the epileptogenic zone (EZ) in patients with frontal or temporal lobe epilepsy. Methods: In this study, we retrospectively analyzed ictal semiology of 489 temporal lobe or frontal lobe seizures recorded over a 6-year period at the Seizure Disorder Center at University of California, Los Angeles in the USA (45 patients) or at the C. Munari Epilepsy Surgery Center at Niguarda Hospital in Milan, Italy (34 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(125 reference statements)
4
6
0
Order By: Relevance
“…Ictal hand signs were found in 54.5% of patients with temporal lobe seizures and 72.5% of those with frontal epilepsies by Ferando et al [13]. The signs identified were cup, fist, pincer, politician's fist, index pointer, and extended hand, which corresponded to some of the signs observed in this study as shown in .…”
Section: Lateralization and Localization Valuessupporting
confidence: 83%
See 2 more Smart Citations
“…Ictal hand signs were found in 54.5% of patients with temporal lobe seizures and 72.5% of those with frontal epilepsies by Ferando et al [13]. The signs identified were cup, fist, pincer, politician's fist, index pointer, and extended hand, which corresponded to some of the signs observed in this study as shown in .…”
Section: Lateralization and Localization Valuessupporting
confidence: 83%
“…1, including their lateralization and localization values. The predominant lateralization and localization information of ictal hand signs has been presented in various studies [11,13,14,16]. Our video EEG monitoring analysis of 145 patients revealed six patients with ictal fist, six with ictal hand extension, five with ictal cup, three with RINCH, two with ictal thumbup, two with ictal pincer, and one each with ictal index pointers.…”
Section: Lateralization and Localization Valuesmentioning
confidence: 68%
See 1 more Smart Citation
“…Hand postures have been associated to focal onset seizures, particularly frontal and temporal onset [2]. Specifically, cup, politician's fist (thumb adjacent to index finger, not abducted as in thumb-up sign) and pincer posture predict temporal lobe localization, whereas fist (thumb opposite to other fingers) and pointing postures predict frontal lobe localization [2].…”
Section: Discussionmentioning
confidence: 99%
“…Index-finger pointing posture is an unusual neurological manifestation commonly observed in patients with craniocervical dystonia, Parkinson’s disease, essential tremor, and epilepsy [1] , [2] . The prevalence of index-finger pointing posture in diverse neurological disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%